Características agronômicas e nutricionais de milho BT ensilado com inoculante enzimo-bacteriano - Moro, Julienne de Geus (2013)
He aim of this study was to evaluate the agronomic characteristics and chemical bromatologic two Bt corn hybrids (30F35H and CD397YH) with silage inoculant bacterial enzymatic. The agronomic evaluations were: plant height, weight, stem diameter, height, ear height and plant population. The plants were separated and weighed in the following fractions: whole plant, leaves + sheath, stem, bracts, panicles, cobs, grains and hair. The experimental design for agronomic evaluations was randomized. The results were submitted to ANOVA and compared using the Tukey test (P <0.05). Plant height and stem diameter did not differ, however, spike height and number of plants/m2 differed among hybrids. The NDF and NDIN were similar for all fractions, since the ADF content differed as to the whole plant, lignin differed in the whole plant, stems and cobs. The IVDMD did not differ among treatments in any of the fractions. The silages were produced in experimental silos (approximately 200 kg), four silos evaluated for each cultivar, Pioneer (30F35H) and Coodetec (CD397YG) with silage inoculant bacterial enzymatic. The experimental design was completely randomized in a 2 x 2 factorial (two maize cultivars, inoculated and control) and four replications. Concentrations of DM, EE, NDF, NDT and IVDMD showed no difference between silage hybrids evaluated. Since the levels of MM, CP, ADF and lignin were different among hybrids. There were differences among hybrids for CHT and the C fraction of carbohydrates, while the content of NFC, fraction A + B1 and B2 fraction did not differ between hybrids. There was no difference between hybrids for silage TDN and for the IVDMD. Also there was no effect of the use of inoculant on the values of CHT and NFC NDF and IVDMD. It is concluded that the hybrid Pionner 30F25H was superior to Coodetec CD 397YG, relative productivity of MV-1 ha, which can be criterion of choice because dilution provides greater production costs in total by area.The main chemical differences bromatologic was observed as the FDA and Lignin, and may also be questions when choosing between cultivars. The nutritional composition of corn silage did not differ in the concentration of TDN and digestibility of silages evaluated in sheep. There was no effect of using bacterial inoculant enzymatic digestibility of dry matter and neutral detergent fiber content of silages.